105 NOX2 NADPH—oxidase a novel target to prevent insulin resistance related endothelial cell dysfunction. (16th May 2012) - Sukumar, P; Viswambharan, H; Imrie, H; Cubbon, R M; Yuldasheva, N; Gage, M; Galloway, S; Skromna, A; Smith, J; Gatenby, K; Beech, D J; Wheatcroft, S B; et al.
Abstract : Introduction: Insulin resistance, a central pathophysiological feature of type 2 diabetes is characterised by a deleterious change in endothelial cell phenotype, a hallmark of which is increased generation of reactive oxygen species. We examined the role of NADPH oxidase and specifically NOX2 NADPH oxidase in insulin resistance induced endothelial cell dysfunction. We studied mice with endothelium specific over expression of a dominant negative insulin receptor (ESMIRO) and mice with whole body haploinsufficiency of the insulin receptor (IR +/− ). Methods: ESMIRO mice, a model of endothelium specific insulin resistance, and IR +/− mice a model of whole body insulin resistance were used to examine the effect of acute and chronic pharmacological inhibition of NADPH oxidase on superoxide production (lucigenin enhanced chemiluminescence) and endothelial function (acetylcholine mediated aortic relaxation). To specifically investigate the role of NOX2, we crossed mice with holoinsufficiency of NOX2 with ESMIRO mice to generate ESMIRO/NOX2 y/− mice. Data expressed as mean±SEM; male mice used for all experiments. Results: Basal superoxide generation in isolated pulmonary endothelial cells (PEC) was increased in both models of insulin resistance (by 130% in ESMIRO and 220% in IR +/− compared to wild type, both p<0.01; n=3 for each group). Pre-treating PEC with gp91ds-tat, a cell permeable specific blocker of NOX subunit assembly and function, reduced the excessive superoxide generation in ESMIRO and IR +/− . Endothelial NO mediated vasorelaxation in aortic rings from ESMIRO and IR +/− was impaired (101%±11% relaxation to 1 μM acetylcholine in wild type, 61%±3% in ESMIRO (n=5, p<0.01); 91%±3% relaxation in wild type, 75%±6% in IR +/− (n=4, p=0.03)). This was restored by pre-incubating rings with gp91ds-tat (92%±6% relaxation in ESMIRO and 93%±6% in IR +/− ). Chronic (4 weeks) administration of gp91-ds tat peptide (using osmotic mini-pump) to ESMIRO and IR +/− mice also restored endothelial dependent relaxation (from 83%±11% to 100%±9% in ESMIRO and to 136%±11% in IR +/− ). NOX2 gene expression was significantly higher in ESMIRO mice. ESMIRO/NOX2 y/− mice with complete deletion of NOX2 had significantly greater relaxation responses to acetylcholine than ESMIRO (77%±6% relaxation in ESMIRO and 100%±4% in ESMIRO/NOX2 y/− ; n=5, p=0.002). Neither pharmacological nor genetic inhibition of NADPH oxidase had any effect on glucose homeostasis. Discussion: These data in complementary models of insulin resistance demonstrate that acute or chronic pharmacological inhibition of NADPH oxidase reduces superoxide generation and improves endothelial function. Specifically targeting NOX2 also restored endothelial function in ESMIRO mice.